(untitled) (Eurasian Medical Research Periodical, 2022)
Laboratory diagnosis of any pathological condition, including acute cholecystitis, contributes to the appropriate therapeutic management. Therefore, our study came to evaluate hepatic biochemical indicators in acute cholecystitis patients. This prospective study was conducted between January 2021 and July 2022 on 120 participants attended to private hospitals located in Kirkuk city, northern Iraq. Informed consent was obtained from each participant, and then the participants were divided into two groups, each group comprising 60 individuals, the first for control and the second for those diagnosed with acute cholecystitis. The biochemical analyzes of the liver indicators required for the study were performed after collecting the serums of all the participants. The laboratory results proved that the hepatic serum indices including ALT, AST, ALP, GGT, and total bilirubin in acute cholecystitis patients were significantly higher compared to the healthy participants. Thus, it was concluded that the apparent high levels of hepatic enzymes in the serum had a prominent role in diagnosing this disease.